The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2007
DOI: 10.1093/icb/icm063
|View full text |Cite
|
Sign up to set email alerts
|

Minireview: Recent progress in hemocyanin research

Abstract: This review summarizes recent highlights of our joint work on the structure, evolution, and function of a family of highly complex proteins, the hemocyanins. They are blue-pigmented oxygen carriers, occurring freely dissolved in the hemolymph of many arthropods and molluscs. They are copper type-3 proteins and bind one dioxygen molecule between two copper atoms in a side-on coordination. They possess between 6 and 160 oxygen-binding sites, and some of them display the highest molecular cooperativity observed i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
112
0
1

Year Published

2008
2008
2023
2023

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 149 publications
(119 citation statements)
references
References 92 publications
5
112
0
1
Order By: Relevance
“…In arcid bivalves Scapharca inaequivalvis, blood oxygen transport mediated by hemoglobin-containing erythrocytes is also impaired by Cd exposure, although in this case the mechanism involves a decrease in hematocrit and hemocyte count, and not in oxygen affinity (Weber et al 1990). Given that the oxygen affinity of respiratory pigments, including hemoglobins and hemocyanins, tends to decrease with increasing temperatures (Burnett 1992, Weber & Vinogradov 2001, Decker et al 2007), the combined action of trace metals, high temperature and low oxygen solubility in the water may strongly limit oxygen uptake and delivery in the respiratory organs of aquatic ectotherms.…”
Section: Energy Supplymentioning
confidence: 99%
“…In arcid bivalves Scapharca inaequivalvis, blood oxygen transport mediated by hemoglobin-containing erythrocytes is also impaired by Cd exposure, although in this case the mechanism involves a decrease in hematocrit and hemocyte count, and not in oxygen affinity (Weber et al 1990). Given that the oxygen affinity of respiratory pigments, including hemoglobins and hemocyanins, tends to decrease with increasing temperatures (Burnett 1992, Weber & Vinogradov 2001, Decker et al 2007), the combined action of trace metals, high temperature and low oxygen solubility in the water may strongly limit oxygen uptake and delivery in the respiratory organs of aquatic ectotherms.…”
Section: Energy Supplymentioning
confidence: 99%
“…These prophenoloxidases are copper-containing enzymes that are closely related to the oxygen transporter hemocyanin. Interestingly, it has been demonstrated that the hemocyanins can be readily converted into phenoloxidases by conformational changes induced by limited proteolysis or chemical treatment (45). In vivo activation of both insect and crustacean hemocyanins has also been reported as an antimicrobial defense response (46,47).…”
Section: And Coptotermes Formosanus (Bab40696) Gastropod Sequences Imentioning
confidence: 99%
“…Their basic structure is composed of ten subunits that are self-assembled into a hollow cylinder known as a decamer. In gastropods, decamers can self-associate face-to-face to form stable dimers or didecamers [1,2]. Inoculating mammals with hemocyanins induces a strong immune response that is characterized by a Th1 cytokine profile.…”
Section: Introductionmentioning
confidence: 99%